OPTIMALISASI PELINDIAN BIJIH MANGAN ASAL TIMOR TENGAH UTARA MENGGUNAKAN H2O2 SEBAGAI PEREDUKSI - Faustina De Yesu Prisila Abi; Rachmat Triandi Tjahjanto; Yuniar Ponco Prananto (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2023)
Optimization of manganese ore leaching process from North Central Timor, Indonesia has been investigated. The final product of the leaching process was MnSO4. Variables that were optimized during the process were volume of H2O2, reaction temperature, and reaction time. The final products were characterized by FTIR, powder-XRD, XRF, and AAS. Experimental data shows that the optimum conditions for the leaching process were 50 mL H2SO4 4 M, 25 mL H2O2 2 M, in which the reaction was done at room temperature for two hours. This optimum condition resulting in 38.2% of Mn extraction with 96.88% purity. Based on powder-XRD, the products were a mixture of crystalline MnSO4.4H2O, MnSO4.5H2O and [NH4]8[Mn8(SO4)12].